Tinjauan Kritis Eksistensialis Karl Theodor Jaspers Terhadap Teknik Rekayasa Genetika Clustered Regularly Interspaced Short Palindromic Repeats - Nur Alifah (Universitas Insan Budi Utomo, 2024)
CRISPR-Cas9 genetic engineering technology has been controversial for many reasons. Genetic privacy and security are major concerns because the genetic information of individuals and their offspring can be misused or exploited. The purpose of this research is to provide an understanding of how an existentialist philosopher might view issues related to human genetic manipulation. This type of research is qualitative research in the field of philosophy related to actual problems. The research model used is library research. The results of the research analysis state that in Karl Jaspers' existentialist thinking, individual freedom and responsibility for these choices are very important. In addition, anxiety is present because of the awareness of freedom and responsibility, as well as the reality of death. Hope is also an important element in human life that relates to transcendence. Relationships with others also affect a person's identity and existenceJaspers also emphasises the importance of direct experience in determining the meaning of life and human existence. In the context of genetic engineering, genetic interference can threaten freedom and alter human essence. Jaspers was also interested in the limits of human existence, including the limits of normality and pathology, truth and lies, and freedom and determinism. Ethical and moral issues related to genetic engineering also arise, including unknown risks and questions about its ethical use.